Analisis Fitur Kebutuhan Konsumen Dengan Metode Kano Untuk Perancangan Web Application D’Cetak - Afwa, Intan Lailya; Sisilia, Kristina; Hidayat, Agus Maolana; Setyorini, Retno (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This study discusses the prioritization of D'Cetak Web Application attributes using the Kano method. The Kano model is used to categorize service feature attributes based on customer satisfaction. This study uses a qualitative approach with the Kano method data analysis technique. The Kano method is a method used to categorize service attributes based on customer satisfaction. The steps in using the Kano method include identifying need attributes, developing Kano questionnaires, distributing questionnaires, and interpreting results. The subjects of this study are Telkom University students who meet the criteria specified by the researcher. Data collection techniques include the use of questionnaires and literature studies. The data validity technique used in this study is the adequacy of references. The results of the study show that there are 10 attributes that fall into the attractive category and 8 attributes that fall into the one dimensional or performance category.